The 'Crossed-Out God' in the Asia-Pacific Religious Efficacy of Public Spheres - Millie, Julian (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2023)
This book explores the evaluations made by religious groups and individuals about the potential of public spheres for religious practice, focussing upon public religion in societies of the Asia-Pacific. Across this region we observe a resurgence of religious traditions, increasing mediatisation of religion, and an inward turn toward conservative political programs. Against this background, relations between religion and public domains are critical influences upon civic inclusion and equal citizenship. In contrast to conventional approaches to religion and public life that focus upon the public potential of religion, chapter authors focus upon the religious potential of public domains, taking the perspectives of religious actors as their points of departure. The book's chapters capture the dynamic nexus between religion and politics in Asia-Pacific public spheres: why would Indonesia's minority Shiite movement strive to develop a public profile in a national environment where it attracts widespread disapproval? What constructions of religion and public space make Banaras so unconducive to female mobility? Why does the success of the social services wing of Australia's Salvation Army create anxiety for its religious wing? What is at stake for followers of Australian Spiritualism when they attend spirit-medium sessions? How are popular Islamic preachers vulnerable to action from Indonesia's civil society organisations? What do media representations of Hajj pilgrimage by Indonesia's presidents have in common with middle-class representations of gender? Why did Indonesia's traditionalist Muslim intellectuals draw heavily upon the ideas of Jürgen Habermas in their theorisations of state-society relations? An epilogue by the Indonesian neo-traditionalist intellectual Ahmad Baso, the most prominent theorist of state-religion relations in that country, overviews the issues against the background of that country's religious and political histories. Julian Millie (PhD Leiden, 2005) is an Australian anthropologist and Indonesianist. He researches the social and political meanings of Islamic rituals and worship practices in Indonesia. His current role is Professor of Indonesian Studies at Monash University.
1. The religious efficacy of public spheres (introduction) -- 2. Mediumship and Evidence in Australian Spiritualism: Conjunctions of Private and Public -- 3. Public faith in action or private sect: The Salvation Army in the present -- 4. Patriarchal Territoriality: Women and the Sacred City of Banaras -- 5. Public Islam and preacher-disruptors in Indonesia: A case study -- 6. Habermas and traditionalist Muslim reflexivity in Indonesia -- 7. Minority Islam in Indonesia's public square: the Shia emergence and its effects -- 8. Social Media Representations of the Muslim Middle-Class: Conspicuous Pilgrimages and the Politics of Public/Private in Indonesia -- 9. Epilogue.
Keywords: Religion and politics; Anthropology of religion; Politics and Religion; Anthropology of Religion